OPTIMIZING THE ROLE OF ARTIFICIAL LIGHTING IN COMMERCIAL BUILDINGS - Nimas Ayu Retno Wulan; Dina Poerwoningsih; Nurhamdoko Bonifacius (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Interior is the most important part in a commercial building because most of the human activity (visitors) happens inside. The interaction between the interior elements with the activity, the behavior, the mood of the visitor takes place in it. Lighting as one of the elements of the interior serves for vision (vision) and create an atmosphere of the interior (aesthetic), in addition to the conditions of a safe and comfortable environment. This paper examines how an artificial lighting system, with the aim of getting an idea of how to optimize the role of artificial lighting in some commercial buildings. The method used is literature study, consisting of lighting theories and the results of research in several commercial buildings.